WAKAF DI INDONESIA POTENSI DAN CARA PENYELESAIANNYA MENURUT PERATURAN PERUNDANG UNDANGAN - Zaidah, Yusna (Syariah: Jurnal Hukum dan Pemikiran, 2014)
This paper will discuss the potential and endowments dispute according to the legislation. Waqf is not just a religious issue or for life people, but for the social and individual problems. Therefore, there are some things that put forward, such that the endowments allow for potential dispute, the validity of the act donating (waqf), and dispute resolution that can be reached through deliberation to reach consensus, if not successful, the dispute can be resolved through mediation, arbitration, and or court